2022
DOI: 10.1055/s-0042-1744499
|View full text |Cite
|
Sign up to set email alerts
|

Necrose avascular pós-cirurgia de Dunn modificada no tratamento do escorregamento da epífise proximal do fêmur*

Abstract: Resumo Objetivo Analisar a incidência da necrose avascular da epífise no tratamento do escorregamento da epífise proximal do fêmur pela técnica de Dunn modificada, correlacionando-a com outras variáveis. Como objetivo secundário, descrevemos outras complicações encontradas. Métodos Estudo retrospectivo com 20 pacientes tratados entre 2009 e 2019, com seguimento de 2 a 12 anos, tratados pela mesma equipe cirúrgica. A análise incluiu características gerais, tempo entre apresentação e procedim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 33 publications
2
3
0
2
Order By: Relevance
“…The prevalence of AVN ranges from 6.5% to 53% in unstable cases in multiple studies found in the literature. 2 5 6 10 16 23 24 34 Our sample presented a rate of AVN of 26% (8 hips), which is comparable to a previously published multicentric American study published in 2013, 11 which only evaluated unstable slips. In a Brazilian SCFE cohort recently published by Valenza et al, 34 an overall AVN rate of 25% was found among stable and unstable slips, which is also compatible with our sample, even though we only studied unstable cases.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The prevalence of AVN ranges from 6.5% to 53% in unstable cases in multiple studies found in the literature. 2 5 6 10 16 23 24 34 Our sample presented a rate of AVN of 26% (8 hips), which is comparable to a previously published multicentric American study published in 2013, 11 which only evaluated unstable slips. In a Brazilian SCFE cohort recently published by Valenza et al, 34 an overall AVN rate of 25% was found among stable and unstable slips, which is also compatible with our sample, even though we only studied unstable cases.…”
Section: Discussionsupporting
confidence: 84%
“… 2 5 6 10 16 23 24 34 Our sample presented a rate of AVN of 26% (8 hips), which is comparable to a previously published multicentric American study published in 2013, 11 which only evaluated unstable slips. In a Brazilian SCFE cohort recently published by Valenza et al, 34 an overall AVN rate of 25% was found among stable and unstable slips, which is also compatible with our sample, even though we only studied unstable cases. It is important to mention that different techniques for capital realignment are used internationally to treat SCFE.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…After Aprato's study, several authors have reported eight additional cases of HI [17,40,41,44] with a prevalence of about 6.6%. However, the etiology of HI was recognized in only two of the eight reported cases: one case was caused by a loose body into the hip joint [41] and the other by the interposition of the in-folded capsule between the femoral head and the acetabular walls [43].…”
Section: Discussionmentioning
confidence: 99%
“…The gradual spread of MDP throughout the world during the last 16 years has changed the approach to SCFE treatment, prompting more and more surgeons to adopt MDP, attracted by the good result obtained with this technique. However, most authors have indicated MDP in moderate to severe SCFE [16,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44], while others have extended the indication to mild SCFE as well [15,[45][46][47]. This new trend has also influenced the indication for "in situ" pinning (ISP) that represents a milestone in SCFE treatment.…”
Section: Discussionmentioning
confidence: 99%